Central corticotropin releasing factor and social stress - Backström, Tobias; Winberg, Svante (Frontiers in Neuroscience, 2013)
Social interactions are a main source of stress in vertebrates. Social stressors, as well as other stressors, activate the hypothalamic-pituitary-adrenal (HPA) axis resulting in glucocorticoid release. One of the main components of the HPA axis is corticotropin releasing factor (CRF). The neuropeptide CRF is part of a peptide family including CRF, urocortin 1-3, urotensin 1-3 and sauvagine. The actions of the CRF family are mediated by at least two different receptors with different anatomical distribution and affinities for the peptides. The CRF peptides affect several behavioral and physiological responses to stress including aggression, feeding and locomotor activity. This review will summarize recent research in vertebrates concerning how social stress interacts with components of the CRF system. Consideration will be taken to the different models used for social stress ranging from social isolation, dyadic interactions, to group dominance hierarchies. Further, the temporal effect of social stressor from acute, intermittent, to chronic will be considered. Finally, strains selected for specific behavior or physiology linked to social stress will also be discussed.